2017
DOI: 10.1002/ana.25094
|View full text |Cite
|
Sign up to set email alerts
|

A variant in PPP4R3A protects against alzheimer‐related metabolic decline

Abstract: Objectives A reduction in glucose metabolism in the posterior cingulate cortex (PCC) predicts conversion to Alzheimer’s disease (AD) and tracks disease progression, signifying its importance in AD. We aimed to use decline in PCC glucose metabolism as a proxy for the development and progression of AD to discover common genetic variants associated with disease vulnerability. Methods We performed a genome-wide association study (GWAS) of decline in PCC [18F] FDG PET measured in Alzheimer’s Disease Neuroimaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…On the NHGRI-EBI GWAS catalog 54 , our results tagged many variants that had been implicated with brain structures, including 7 in van der Meer, et al 55 for hippocampal subfield volumes, 7 in Verhaaren, et al 56 for cerebral white matter hyperintensity (WMH) burden, 5 in Vojinovic, et al 57 for lateral ventricular volume, 5 in Rutten-Jacobs, et al 26 for WMH and white matter integrity, 2 in Klein, et al 58 for intracranial volume, 2 in Hibar, et al 59 for subcortical brain region volumes, 2 in Fornage, et al 28 for WMH burden, 1 in Elliott, et al 23 for brain imaging measurements, 1 in Luo, et al 60 for voxel-wise brain imaging measurement, 1 in Hashimoto, et al 61 for superior frontal gyrus grey matter volume, 1 in Ikram, et al 62 for intracranial volume, and 1 in Sprooten, et al 63 for global FA (Supplementary Table 14). When the significance threshold was relaxed to 5 × 10 -8 , we tagged variants reported in more previous studies, such as 2 in Shen, et al 64 for brain imaging measurements, 2 in Chung, et al 65 for hippocampal volume in dementia, 1 in Chen, et al 66 for putamen volume, and 1 in Christopher, et al 67 for posterior cingulate cortex (Supplementary Table 15).…”
Section: Concordance With Previous Gwasmentioning
confidence: 99%
“…On the NHGRI-EBI GWAS catalog 54 , our results tagged many variants that had been implicated with brain structures, including 7 in van der Meer, et al 55 for hippocampal subfield volumes, 7 in Verhaaren, et al 56 for cerebral white matter hyperintensity (WMH) burden, 5 in Vojinovic, et al 57 for lateral ventricular volume, 5 in Rutten-Jacobs, et al 26 for WMH and white matter integrity, 2 in Klein, et al 58 for intracranial volume, 2 in Hibar, et al 59 for subcortical brain region volumes, 2 in Fornage, et al 28 for WMH burden, 1 in Elliott, et al 23 for brain imaging measurements, 1 in Luo, et al 60 for voxel-wise brain imaging measurement, 1 in Hashimoto, et al 61 for superior frontal gyrus grey matter volume, 1 in Ikram, et al 62 for intracranial volume, and 1 in Sprooten, et al 63 for global FA (Supplementary Table 14). When the significance threshold was relaxed to 5 × 10 -8 , we tagged variants reported in more previous studies, such as 2 in Shen, et al 64 for brain imaging measurements, 2 in Chung, et al 65 for hippocampal volume in dementia, 1 in Chen, et al 66 for putamen volume, and 1 in Christopher, et al 67 for posterior cingulate cortex (Supplementary Table 15).…”
Section: Concordance With Previous Gwasmentioning
confidence: 99%
“…SERPINB1 rs316341 and SPI1 rs1057233 were associated with CSF Aβ levels (Deming et al, 2017;Huang et al, 2017a). The association between decline in brain glucose metabolism and PPP4R3A rs2273647 was recently reported (Christopher et al, 2017). Three ACE polymorphisms (rs4968782, rs4316, rs4343) were associated with CSF levels of ACE gene product (Kauwe et al, 2014).…”
Section: Genes Associated With Ad Biomarker Levelsmentioning
confidence: 92%
“…Zinc-finger ZCWPW1 is another gene involved in histone modification and epigenetic regulation (He et al, 2010 ). PPP4R3A rs2273647 showed protective effect in risk for AD (Christopher et al, 2017 ). It encodes a regulatory subunit PPP4R3A of serine/threonine phosphatase (Chowdhury et al, 2008 ).…”
Section: Genes and Molecular Pathways Implicated In MCI And Ad Riskmentioning
confidence: 99%
“…PPP4R3A deficiency prevented neural stem cells from differentiating, leading to neurogenesis deficits during mouse cortical development (Lyu et al, 2013, Moon et al, 2017. A protective PPP4R3A variant, rs2273647-T, was identified in AD patients that help to slow the onset and progression of AD pathology via reduced glucose uptake by the brain (Christopher et al, 2017). In a previous study, we revealed that PPP4R3A acts as a genetic modifier of spinocerebellar atrophy type 3.…”
Section: Introductionmentioning
confidence: 97%